Primary amenorrhea - Prötzel Pinedo, Ana (2015)
The most common causes of primary amenorrhea include Turner syndrome (TS), androgen insensitivity syndrome (AIS), and complete or partial absence of the uterus and vagina. It is useful for diagnosis is useful to link this symptom with development of secondary sexual characteristics, height and presence or absence of genital anomalies. We recommend the following genetic classification: A. Amenorrhea with delayed puberty: Hypergonadotropic hypogonadism: Turner syndrome (TS), pure gonadal dysgenesis XY or Swyer’s syndrome (GDXY) and pure gonadal dysgenesis XX, Perrault syndrome and other forms of XX gonadal dysgenesis (GDXX) Hypogonadotropic hypogonadism: Kallmann syndrome (KS) B. Amenorrhea with normal puberty: Polycystic ovary disease Non classical congenital adrenal hyperplasia Mayer-Rokitansky-Küster-Hauser’s syndrome (MRKHS) and Androgen insensitivity syndrome (AIS)